Spatiotemporal Dynamics of Carbon Emissions and the Role of Land-Use Change: A County-Level Analysis in Ganzhou, China - Xi, Sichen (International Journal of Natural Resources and Environmental Studies, 2026)
Ganzhou has experienced rapid land-use and socioeconomic transformation over the past two decades, yet county-level analyses of carbon emission dynamics and their land-use drivers remain limited. This study examines the spatiotemporal evolution of county-level CO₂ emissions in Ganzhou from 2000 to 2020 using emission data from the China Emission Accounts and Datasets, land-use maps, and socioeconomic statistics. Spatial analytical methods, including Moran’s I and the standard deviational ellipse, together with landscape metrics and correlation analysis, were applied to explore emission patterns and their relationship with land-use structure. Results show that total CO₂ emissions increased from 9.59 Mt in 2000 to 36.36 Mt in 2020, although the growth rate slowed after 2010. The spatial pattern shifted from a “central high–peripheral low” structure to a more dispersed pattern characterized by “central > northeast > south > west.” Built-up land expansion and greater patch aggregation are significantly positively correlated with emissions, whereas larger and more connected forest patches show significant negative correlations. These findings highlight the importance of controlling urban expansion, improving forest connectivity, and promoting coordinated regional mitigation strategies to support carbon reduction and sink enhancement.